2016
DOI: 10.1002/marc.201670039
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Rapid Commun. 9/2016

Abstract: Back Cover: The shish-kebab superstructure of poly(lactic acid) stereocomplex was developed in a transient and strong shear flow. The shear-aligned stereocomplex chains were preferentially assembled into the central shish, while the crystal form of the lateral kebabs showed strong dependency on the crystallization temperature. Further details can be found in the article by L. Xie, H. Xu, Z.-M. Li, and M. Hakkarainen* on page 745.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…observed that SC remained spherulitic and the spherulites growth rate did not change at the applied shear conditions. However, Xie et al . found that SC formed preferentially as central shish under shear flow.…”
Section: Introductionmentioning
confidence: 98%
“…observed that SC remained spherulitic and the spherulites growth rate did not change at the applied shear conditions. However, Xie et al . found that SC formed preferentially as central shish under shear flow.…”
Section: Introductionmentioning
confidence: 98%
“…9 In past decades, there is a growing realization that the key to address the above dilemma and achieve high-performance PLA lies in sufficient control of condensed structure, especially orientation structure. 10 Plastic deformation of SCP is an important approach to produce orientation structures. It has been widely proved that the plastic deformation of crystalline phase proceeds mainly through crystallographic slip.…”
Section: Introductionmentioning
confidence: 99%